Analysis of the Application of the Discovery Learning Model to Students' Creative Thinking Ability in Reaction Rate Material - Niski Nadila; Louis-Charl Cloete Coetzee; Beatrice Arwenyo (Indonesian Journal of Education Research (IJoER), 2023)
Purpose of the study: The purpose of this study was to describe and determine the relationship between the implementation of the discovery learning model in the matter of the rate of reaction with the students' creative thinking abilities. Methodology: This research is a type of correlational descriptive research. The sampling technique used in this study is Simple Random Sampling. The instrument used in this research is the observation sheet. Data analysis techniques using normality and homogeneity tests. After the prerequisite test is carried out, the hypothesis test is then carried out. Main Findings: The results of this research are that the application of the Discovery Learning model to reaction rate material can be carried out very well. This is because the teacher corrects errors in applying the model at the next meeting and there is a relationship between the application of the Discovery Learning model and students' creative thinking abilities in the reaction rate material in class XI in the medium category. Novelty/Originality of this study: Provide information about the implementation of discovery learning learning models and their correlation with students' creative thinking abilities.